Diversidade sexual na escola: análise de dois vídeos educativos - Silva, Priscila Leylane Costa da (2021)
This research is entitled “Sexual diversity at school: an analysis of two educational videos. Its general objective is to analyze the educational process on sexual diversity from the analysis of two educational videos released in the national media. The specific objectives were: Observe in the testimonies of the participants in the videos, conceptions about the theme of diversity sexual in the context of the school space; verify implications of teaching about sexual diversity in training and learning of students and teachers; problematize teacher training in light of sexual diversity in the curricular proposals of the Pedagogy course. The research proposal it occurred from the observations of the internships and in the everyday experiences of the university. This one study uses a qualitative exploratory approach from the perspective of some theorists, among them, Michel Foucault. To deepen the research, two videos were used. documentaries that are available on social media. As a result, we point out four categories that arise from this analysis: 1. Bodies, Gender, Sexualities: what awaits us at school. 2. The role of school in the sexual regulation of bodies: you need to change your way. 3. Psychologizing sexuality and religious morality: "You know that God abhors this, right? 4. Educators' conceptions about diversity at school. As a result of the analyses, we understand that there are possibilities for confronting and combating homophobia through a curriculum focused on sexual diversity and teacher training.